The Role of History and Political Studies in Post-Genocide Reconstruction and Development - Rutayisire, Paul; Mulinda, Charles Kabwete (Journal of African Conflicts and Peace Studies, 2013)
This paper argues for complementarity between social sciences, such as history and political studies on the one hand, and science and technology on the other hand. It insists that Africa and Rwanda in particular need the discipline of history in conjunction with science and technology in order to teach knowledge that is complete and to target African renaissance, that is, sustainable development and sustainable peace. It also makes an advocacy for History and Political Science disciplines because of particular crises that those programmes are currently facing at the National University of Rwanda (NUR). But it does also put those crises in a wider context by showing the trajectory of History since the postindependence period. It finally stresses the contribution that historians and political scientists at NUR have made for Rwanda since 1994 in the post-genocide reconstruction and in development.
Keywords: Genocide; Reconstruction; Development